Knowing Students' Characteristics: Opportunities to Adapt Physical Education Teaching - Kirch, Alina; Schnitzius, Melina; Spengler, Sarah; Blaschke, Simon; Mess, Filip (Frontiers in Psychology, 2021)
Physical Education (PE) aims to convey the joy of exercise and by this educate students to lifelong physical activeness. Student motivation in PE decreases during the school career. This study therefore comprehensively analyses student characteristics determining motivation in PE: General Personality Traits, Physical Self-Concept, Achievement Motive, Motives to be physically active and Sports Interest. This contribution aims to describe students’ prerequisites in the PE context by using an aggregated assessment of the abovementioned general plus sport specific characteristics and to detect gender, class and school type differences. In total, 1,740 German secondary school students (58.1% female, M=14.39 years) participate in a cross-sectional questionnaire survey. Descriptive analyses and between subjects MANOVAs followed by univariate ANOVAs with pairwise multiple comparison tests are applied. Gender explains the largest proportion of variance across all characteristics. Regarding individual dimensions, genders differed on 12, grades on four and school types on 11 out of 19 dimensions. PE teachers must adapt teaching to different gender dispositions. In general, group differences ascribe special meaning to student perception and teaching behavior. Findings are discussed in terms of their contribution to the research area and their implementation in teaching practice as well as in PE teacher education or professional training, e.g. aligned teaching methods, arranged learning atmospheres or adjusted content design of PE lessons.